2019
DOI: 10.1002/jcp.29278
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel LncRNA targeting Smad2/PKCα signal pathway to negatively regulate malignant progression of glioblastoma

Abstract: Glioblastoma multiforme (GBM) is a highly proliferative cancer with generally poor prognosis and accumulating evidence has highlighted the potential of long noncoding RNAs (lncRNAs) in the biological behaviors of glioma cells. This study focused on the identification of lncRNAs to identify targets for possible GBM prognosis. Microarray expression profiling found that 1,759 lncRNAs and 3,026 messenger RNAs (mRNAs) were upregulated, and 1932s lncRNA and 2,979 mRNAs were downregulated in GBM. Bioinformatics analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In recent years, more and more studies have focused on lncRNAs as tumor diagnostic markers and potential therapeutic targets. Numerous researches have shown that lncRNAs play an important regulatory role in the development of various cancers, including glioma [3][4][5]. For example, linc00319 expresses at a high level in glioma and is significantly associated with poor prognosis of glioma patients, while knockdown of linc00319 impairs cell proliferation, arrests cell cycle and induces cell apoptosis of glioma cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, more and more studies have focused on lncRNAs as tumor diagnostic markers and potential therapeutic targets. Numerous researches have shown that lncRNAs play an important regulatory role in the development of various cancers, including glioma [3][4][5]. For example, linc00319 expresses at a high level in glioma and is significantly associated with poor prognosis of glioma patients, while knockdown of linc00319 impairs cell proliferation, arrests cell cycle and induces cell apoptosis of glioma cells [6].…”
Section: Introductionmentioning
confidence: 99%
“…Li et al showed that LINC00645 could promote EMT, which was indispensable in the invasion and migration of glioma cells involving TGF-b by regulating the miR-205-3p-ZEB1 axis; thus, LINC00645 could be a prognostic indicator for glioma (57). A novel lncRNA-TOCN that targets the Smad2/PKCa signaling pathway to inhibit malignant progression of glioma was highlighted by Tang et al and could serve as a prognostic indicator of GBM (58). The expression of multiple lncRNAs has been documented to correlate with the malignancy of gliomas and to be involved in their malignant progression, providing powerful theoretical evidence for their application as diagnostic and prognostic markers.…”
Section: Lncrnas As Diagnostic and Prognostic Biomarkers Of Gliomasmentioning
confidence: 99%
“…In the initial stage of lncRNA research, some scholars suggested that there is a difference in the expression of lncRNAs between tumor tissues and adjacent normal tissues. An increasing number of studies 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 have shown that lncRNAs may play an important biological role in the regulation of cancer development, as the biological function of lncRNAs in carcinomas is to promote cancer cell proliferation and invasion, suppress cancer cell proliferation and invasion, estimate the prognosis and efficacy, and act as potential biomarkers, as summarized in Table 1 .…”
Section: Biological Function Of Lncrnas In Carcinomasmentioning
confidence: 99%